2022
DOI: 10.1007/s13201-022-01570-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of pharmaceutical drugs in a municipal wastewater and overview of associated risks

Abstract: Pharmaceuticals compounds are the emerging contaminants known for their refractory and environmental persistence, which pose threat to flora and fauna. In the present study, the occurrence and possible contamination sources of four drugs, namely paracetamol, diclofenac, salbutamol and ceftriaxone in wastewater of Mysuru, India, were investigated. The said pharma compounds were analyzed in the effluent of select health care establishments and municipal wastewater treatment plant (MWWTP). The results revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Even though ceftriaxone is one of the most prescribed antibiotics in health facilities, there is little information regarding its occurrence in the environment [ 43 ]. A recent study in India found high levels of ceftriaxone (from 1.25 to 29.15 µg/mL) in hospital effluent [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though ceftriaxone is one of the most prescribed antibiotics in health facilities, there is little information regarding its occurrence in the environment [ 43 ]. A recent study in India found high levels of ceftriaxone (from 1.25 to 29.15 µg/mL) in hospital effluent [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, research was conducted in India to examine the effluent of selected health care establishments and municipal wastewater treatment plants. The study findings indicated that the results for ceftriaxone ranged from 1.25–29.15 µg/mL [ 32 ]. The antibiotics have been proven in several publications as emergent contaminants in the aquatic environments around the world.…”
Section: Introductionmentioning
confidence: 99%